1993
DOI: 10.1111/j.1365-2273.1993.tb00541.x
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the complications of paediatric tonsillectomy, adenoidectomy and adenotonsillectomy

Abstract: Tonsillectomy, adenoidectomy and adenotonsillectomy are among the commonest surgical procedures undertaken in children. The notes of 413 consecutive children having tonsillectomy, adenoidectomy or adenotonsillectomy were analysed retrospectively to determine complication rates. Of the total number of children, 5.6% had at least one complication, the most common of which was haemorrhage occurring as a first complication in 3.9% (16 children). Three children with bleeding required active treatment (0.7%), one re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 5 publications
3
38
1
2
Order By: Relevance
“…The primary major hemorrhage incidence was 0.37% and primary minor hemorrhage incidence was 0.6% after day stay tonsillectomy in children. These incidences are comparable to those reported from British centers [11,12] that have a similar medical system to that in New Zealand. Hellier et al [11] reported a 0.3% incidence of major hemorrhage with a total primary hemorrhage rate of 0.97% during a period 1995-1997 (n = 928).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The primary major hemorrhage incidence was 0.37% and primary minor hemorrhage incidence was 0.6% after day stay tonsillectomy in children. These incidences are comparable to those reported from British centers [11,12] that have a similar medical system to that in New Zealand. Hellier et al [11] reported a 0.3% incidence of major hemorrhage with a total primary hemorrhage rate of 0.97% during a period 1995-1997 (n = 928).…”
Section: Discussionsupporting
confidence: 89%
“…Kendrick and Gibbin [12] report a major hemorrhage incidence of 0.7% (n = 413). Although day stay tonsillectomy remains controversial in parts of Europe [11][12][13][14][15][16], experience has been gained in North America [7,8,[17][18][19][20][21][22][23][24][25]. Literature reviews suggest primary hemorrhage rates of 1-3% and secondary hemorrhage rates of 0.15-6.4% [26,27] Most series are small and depend on the definition of hemorrhage [28,29].…”
Section: Discussionmentioning
confidence: 96%
“…Although these studies may have been useful in providing additional background information, they would not have been specifically useful for both, the qualitative and quantitative portions of this meta-analysis. On further review of the remaining 18 articles, 7 were withdrawn due to a lack of data regarding the primary clinical outcome of interest [9][10][11][12][13][14][15], and 5 were withdrawn due to the absence of a control 856 S. Iyer et al [16][17][18][19][20]. The seven remaining studies with usable information on post-operative outcomes of interest were included in the qualitative portion of this meta-analysis [21][22][23][24][25][26][27].…”
Section: Trial Flowmentioning
confidence: 99%
“…None of the operative techniques seems to be significantly more prone to reactionary haemorrhage than the others. Likewise it's incidence is not related to grade and seniority of the surgeon [8] . A review on secondary haemorrhage suggests that it may be more common than widely appreciated, occurring in about 9% of cases.…”
Section: Complications Of Tonsillectomymentioning
confidence: 94%